HUBUNGAN POLA MAKAN DENGAN KEJADIAN DISPEPSIA - Sumarni Sumarni; Dina Andriani (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
In the life of the general public, dyspepsia is often equated with heartburn, because there are similarities in symptoms between the two. This assumption is actually not quite right, because the word ulcer comes from Dutch, which means stomach, while the word dyspepsia comes from Greek, which consists of two words namely